Nonlinear vibrations of orthogonal mechanism of shaking table - Bissembayev, Kuatbay; Iskakov, Zharilkassin (Zielona Góra: Uniwersytet Zielonogórski)
The dynamics of orthogonal mechanism in the presence of a shaking table of fixed cargo is studied. The focus is on the vibrational motion of the mechanism in slow-speed motor rotation. The analysis of the solutions for motion nonlinear equations showed that the angular velocity of the guiding link oscillates according to the harmonic law about a mean value. The character of changing its amplitude, depending on the weight of the cargo and the length of the guiding link, is determined. Dependence of the mean angular velocity on the motor torque is set.
Keywords: orthogonal mechanism; dynamics; asymptotic method; essentially nonlinearity; stability